Effect of Zinc-selenium Complex (Selcon7) Supplementation in Broiler in Prevention of Infectious Bursal Disease - Saha, B.C.; Das, P.M.; Das, S. (International Journal of Poultry Science, 2010)
A zinc-selenium complex (Selcon®) was evaluated for the prevention of IBDV infection in broilers. Chicks were reared in relative isolation with optimum temperature, water and feeds. They were divided into 4 different groups named A1, B1, A2 and B2; having 3 replications each. Among them Groups A1 and B1 were uninfected group of which Group B1 was supplemented with Selcon®. The rest 2 groups (A2 and B2) were Infected (challenge) group of which Group B2 were supplemented with Selcon®as a preventive measure. At 28 days of age all the birds of challenge Groups (A2 and B2) were inoculated with field homogenates of Infectious Bursal Disease (IBD) virus. The birds were observed for clinical signs, morbidity and mortality at every 6 h interval upto 10 days post infection. Three birds from each of the four groups of three replications were sacrificed at 0, 3 and 6 days post infection and bursa/body weight ratio was determined. Part of bursal tissues were fixed in formalin and processed for bursal lesion scoring along with spleen, thymus, liver and kidney tissues by histopathological study. Selcon® treated IBDV challenged birds of Group B2 revealed 44.44% overall cumulative morbidity and 2.22% overall cumulative mortality, while Selcon® untreated IBDV challenged birds of Group A2 revealed 60.00% overall cumulative morbidity and 11.11% overall cumulative mortality. Results also showed significant difference (p>0.05) in bursa/body weight ratio between Selcon® treated and untreated groups, that overall bursa/body weight ratio in birds of Group B2 was highest (1.30"0.44) and lowest (1.23"0.42) in those of Group A2 had at 6 days post infection. The bursal lesion scores of Group B2 were lower than Group A2. There was no significant variation among the histopathological lesions of spleen, thymus, liver and kidneys of different groups. It may be concluded that supplementation of Selcon® to broiler diets as a preventive measure provides a satisfactory level of protection against morbidity and mortality in IBD.